Investigation of the Wave Field around a Monopile due to Long Crested Irregular Waves in Moderate Steepness - Herdayanditya, Ivandito; Streicher, Maximilian; Lataire, Evert; Rauwoens, Pieter (Journal of Coastal and Hydraulic Structures, 2024)
Monopile foundations are the most built foundations in the offshore wind industry. The diameter is also expected to increase in the near future to accomodate for larger wind turbines in deeper water depths. The large monopile diameter imposes additional challenge in planning the marine operations near the monopile, as the monopile can no longer be treated as a transparent monopile (i.e. the monopile gives negligible impact on the incident waves). Proper wave field estimation around the monopile that also accounts for the monopile existence is needed to assure the safety of the operations. Investigation of the wave field around a monopile due to long crested irregular incident waves is provided in the present study. Experimental study was performed with different irregular wave properties, varying the wave steepness and wave diffraction number. The present study explores further the available experimental studies that focus mostly on the runup of the monopile. Initially, Linear Transfer Function (LTF) of the wave field around a monopile from the experimental study is compared to the linear theory, which is found to match well in the high energy frequency range. The LTF differs with the linear theory in the low and high frequency ranges, indicating pronounced nonlinear effect in those frequency ranges. Further, time series analyis is also performed via exceedance probability analysis and significant value computation. It is found that the nonlinearity appears in the crest properties of the wave field around a monopile, while the wave height properties can still be predicted well with the linear theory. Moreover, Wave Type II, wave that travels in the clockwise/anti-clockwise direction around a monopile and not in radial direction, is seen to influence the crest properties.